Field emission of GaN nanofilms on Si substrates enhanced by hydrogen plasma treatment. (3rd February 2021) - Song, Zhi-Wei; Wang, Changhao; Guo, Gen-Cai; Yang, Meng-Qi; Liang, Qi; Wang, Bo; Chu, Wei-Guo; Wang, Ru-Zhi
Abstract: The (002) oriented GaN nanostructured films prepared by pulsed laser deposition (PLD) on n-type Si (100) substrates were treated by H- and O-plasma, finding both treatments do not make the sizable changes in crystalline structure and morphology of GaN nanofilms. However, the field emission (FE) performance of GaN nanofilms is considerably improved by H-plasma treatment (H-GaN) but deteriorated by O-plasma treatment (O-GaN). The turn-on fields, Eon, for H- and O-plasma treated GaN nanofilms are determined to be 0.52 and 1.79 V μ m −1, respectively, in contrast with that of pristine GaN nanofilms, 0.95 V μ m −1 . The improvement of FE performance by the H-plasma treatments could be attributed to the reasons of the reduced surface potential barrier, the increased electron concentration, the increased surface conductivity, and the increased effective emission area. The first-principles calculations represents that the experimental and theoretical work function results have the same trend with the descending sequence of O-plasma treated GaN > pristine GaN > the H-plasma treated GaN.